2005
DOI: 10.1111/j.1471-4159.2005.03377.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased nuclear factor‐erythroid 2 p45‐related factor 2 activity protects SH‐SY5Y cells against oxidative damage

Abstract: The ability of cells to control the balance between the generation and quenching of reactive oxygen species is important in combating potentially damaging effects of oxidative stress. One mechanism that cells use to maintain redox homeostasis is the antioxidant response pathway. Antioxidant response elements (AREs) are cis-acting elements located in regulatory regions of antioxidant and phase II detoxification genes. Nuclear factor-erythroid 2 p45-related factor 2 (Nrf2) is a member of the Cap 'n' Collar famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…These findings are consistent with our previous report documenting that Nrf2 signaling protects SH-SY5Y cells from 6-OHDA but not MPP ? toxicity [46].…”
Section: Effects Of Antioxidants On the Genomic Responsementioning
confidence: 99%
“…These findings are consistent with our previous report documenting that Nrf2 signaling protects SH-SY5Y cells from 6-OHDA but not MPP ? toxicity [46].…”
Section: Effects Of Antioxidants On the Genomic Responsementioning
confidence: 99%
“…Previous studies have demonstrated that Nrf2-dependent transcription can prevent ROSinduced apoptosis in neurons and astrocytes in vitro (Cao et al, 2005;Kraft et al, 2004;Lee et al, 2003a, b;Shih et al, 2003). Several lines of evidence suggest that chemical induction of antioxidants and detoxification genes through Nrf2-ARE signaling protects against a number of different oxidative insults, including H 2 O 2 , 6-hydroxydopamine (6-OHDA) and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) (Lee et al, 2003a, b;Cao et al, 2005;Kraft et al, 2004;Shih et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that chemical induction of antioxidants and detoxification genes through Nrf2-ARE signaling protects against a number of different oxidative insults, including H 2 O 2 , 6-hydroxydopamine (6-OHDA) and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) (Lee et al, 2003a, b;Cao et al, 2005;Kraft et al, 2004;Shih et al, 2003). Recently, we demonstrated that Nrf2-dependent transcription activated by tert-Butylhydroquinone (t BHQ), a known inducer of Nrf2-mediated transcription, can prevent DM-induced oxidative stress in PC12 cells through translocation of Nrf2 and increased HO-1 gene expression (Li et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 drives the expression of detoxification enzymes, such as NQO1 [NAD(P)H quinone oxidoreductase 1] and Hmox-1, and enzymes that generate antioxidant molecules, such as glutathione (20,21). Nrf2 function and the expression of its regulated genes, including NQO1, have been implicated in the risk and͞or prevention of both cancer and PD (22)(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%